Imagined geographies in the Indo-Tibetan borderlands : culture, politics, place - Gohain, Swargajyoti (Asian borderlands., 2020)
This book is an ethnography of culture and politics in Monyul, a Tibetan Buddhist cultural region in west Arunachal Pradesh, Northeast India. For nearly three centuries, Monyul was part of the Tibetan state, and the Monpas, as the communities inhabiting this region are collectively known, participated in trans-Himalayan trade and pilgrimage. Following the colonial demarcation of the Indo-Tibetan boundary in 1914, the fall of the Tibetan state in 1951, and the India-China boundary war in 1962, Monyul was gradually integrated into India and the Monpas became one of the Scheduled Tribes of India. In 2003, the Monpas began a demand for autonomy, under the leadership of Tsona Gontse Rinpoche. This book examines the narratives and politics of the autonomy movement regarding language, place-names, and trans-border kinship, against the backdrop of the India-China border dispute. It explores how the Monpas negotiate multiple identities to imagine new forms of community that transcend regional and national borders.